The Implementation of Restorative Justice in the Resolution of Minor Criminal Offenses at the Sragen Police Department - Abdi, Ghulam Muhammad; Putri, Hanuring Ayu Ardhani; Suparwi, Suparwi (Jurnal Ilmu Hukum Kyadiren, 2026)
This study aims to examine the implementation of restorative justice in the resolution of minor criminal cases at the Sragen Police Department. The research employs an empirical method using a case study design and a sociological approach that conceptualizes law not merely as a set of written norms but as a social phenomenon operating within society. Data were collected through observations, interviews, and a review of relevant literature focusing on the stages of restorative justice implementation and the factors hindering its effectiveness. The findings indicate that the restorative justice process begins with the submission of a formal request, followed by investigators’ assessment of case eligibility, a mediation process to achieve mutual agreement, and the formalization of the outcome through a written agreement between the parties. However, its implementation faces several obstacles, including limited institutional resources, insufficient understanding among law enforcement officers, disagreements among the parties involved, logistical and scheduling constraints, time limitations, and public perceptions of justice that generate skepticism toward restorative mechanisms. Accordingly, effective solutions are required. The Sragen Police Department should strengthen institutional commitment and regulatory frameworks to ensure that restorative justice is implemented effectively and develops into an embedded organizational culture.